2015
DOI: 10.1002/app.42504
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of polypropylene/modified basalt fabric composites

Abstract: Basalt fabric (BF) was first treated with silane coupling agent KH550, modified basalt fabric (MBF) was obtained. Then MBF were molded with polypropylene (PP) matrix, and polypropylene/modified basalt fabrics (PP/MBF) composites were obtained. The influence of concentration and treating time of KH550 on MBF were characterized by hydrophilicity and lipophilicity. The tensile strength and morphology of basalt fabric were tested by single filament strength tester and scanning electron microscopy. The mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…The increase in the T g values of the composites could be evidently connected by the progressive incorporation of the TBFs within the resin matrix. Guo et al . reported that the high fiber/matrix adhesion could strongly lower the polymer chain mobility and consequently increase the T g of the produced composites.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The increase in the T g values of the composites could be evidently connected by the progressive incorporation of the TBFs within the resin matrix. Guo et al . reported that the high fiber/matrix adhesion could strongly lower the polymer chain mobility and consequently increase the T g of the produced composites.…”
Section: Resultssupporting
confidence: 85%
“…reported that the high fiber/matrix adhesion could strongly lower the polymer chain mobility and consequently increase the T g of the produced composites. Hence, the increase in the T g could be justified by the better interfacial adhesion of the TBFs within the CE/BOZ resin achieved by using the SCA, which might restrict the polymer chain mobility . To clarify more, the addition of TBFs to the CE/BOZ resin acted as a hindrance and later increased the heterogeneity of the crosslinked network of the reinforced polymer composites.…”
Section: Resultsmentioning
confidence: 99%
“…KH550 (NH 2 CH 2 CH 2 CH 2 Si(OC 2 H 5 ) 3 ), an economical organo-silane, was adopted in this study. Silane treatment has proved to be a low-cost and efficient method to endow the fiber-matrix an improved interfacial bonding [26][27][28].…”
Section: Modification Of Basalt Fibermentioning
confidence: 99%
“…Basalt fiber-reinforced plastics (BFRPs) are newly emerging composite materials due to their being recyclable, cost effective, and lightweight [1][2][3][4]. Basalt fiber (BF), produced by abundant natural basalt rocks, is a promising fiber reinforcement, which endows basalt fiber with excellent chemical, weather, and heat resistance [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…For examples, Attia et al [ 18 ] synthesized an organic polyaniline directly on the surface of BF and formed an organic polymer shell on the surface of the inorganic fiber—the tensile strength property was enhanced by 38% and 53% compared to blank and unmodified basalts, respectively. Guo et al [ 19 ] treated BF by using the economical silane agent γ-aminopropyl triethoxysilane (KH550) as a modifier, which showed 194.12% enhancement in impact strength compared to that of pure polypropylene (PP). Zhang et al [ 20 ] modified BF by grafting organic/inorganic composites, and attaching a biofilm rich in microorganisms for wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%